New placement of the leafhopper genus Idioceroides Matsumura (Hemiptera: Cicadellidae: Idiocerinae), with description of a new species - Zhang, B.; Viraktamath, C. A. (Zootaxa, 2009)
The leafhopper genus Idioceroides Matsumura is transferred back to Idiocerinae from Agalliinae where it was erroneously placed. A new species, Idioceroides sichuanensis n. sp. is described and illustrated from Sichuan, China. A key is provided to separate the new species from the only other known species, I. tettigoniformis Matsumura from Taiwan and the female genitalia for species of the genus are described for the first time.